Efektifitas Eye Exercise terhadap Penurunan Tingkat Asthenopia pada Pegawai Inspektorat Daerah Provinsi NTT - Istonia Hermolinda Waang; Luh Putu Ruliati; Jacob Matheos Ratu; Anderias Umbu Roga; Noorce Christina Berek (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
The use of computers or laptops by formal workers in offices is very high in the current era of digitization, it can cause eye fatigue or asthenopia if done for a long time without resting the eyes.  This study aims to determine the effectiveness of eye exercise in reducing the level of asthenopia or eye fatigue in employees of the Regional Inspectorate of NTT Province. This research is aquasi-experimental research using Two Group Pretest Post-Test. The population in this study was 89 people with a research sample of 18 people in the eye exercise intervention group and 18 people in the 20-20-20 method intervention group taken using the random allocation method. Data analysis used univariate analysis and the Independent Sample t-Test (Mann Withney). The results of the study showed that the level of eye strain in both intervention groups decreased after doing eye exercises and the 20-20-20 method. There was a difference in the mean value of eye fatigue between the two intervention groups of 3.89 with a significance of 0.03. The conclusion of this research is that the 20-20-20 method is effective in reducing the level of eye fatigue in employees of the Regional Inspectorate of NTT Province.